Income inequality, growth and elite taxation in Brazil: New evidence combining survey and fiscal data, 2001-2015 - Marc Morgan (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
This paper analyses the pre-tax inequality in the income that individuals actually receive in Brazil and the role of the personal income tax in regulating these incomes. We produce a new distributional series of fiscal income, consistently combining annual and nationally representative household survey data with detailed information on income tax declarations recently released by the Brazilian Federal Tax Office. Our results provide a sharp upward revision of the official estimates of inequality in Brazil but maintain the decreasing inequality trends, even though they are less pronounced than previously measured. The exceptionally large concentration of income at the top is noteworthy, as is its relative stability over time. The income share of the wealthiest 10 per cent of the population fell from 54.6 per cent to 53.0 per cent of pre-tax fiscal income between 2001 and 2015, while the share of the poorest 50 per cent of the population rose from 10.6 per cent to 12.6 per cent. Brazil's squeezed middle 40 per cent of the distribution experienced a slight drop in its share, from 34.8 per cent to 34.4 per cent. Despite strong average income growth, the poorest 50 per cent only made moderate gains, which came at the expense of smaller shares for the middle and the top. Over the short to medium term, it is the level of average income of the bottom that matters more than its growth. We show that the role of the personal income tax in regulating incomes in Brazil is very limited, because the majority of the income of elites in Brazil is not subject to the tax. This explains the lower effective tax liability that is observed for upper income groups and illustrates that the personal income tax is not a progressive policy tool in Brazil, violating the principles of horizontal equity and vertical equity. This motivates the creation of a simplified and comprehensive personal income tax that would incorporate all income categories along a single or dual tax regime. [...]
Keywords: 330; Income; inequality; growth; elite; taxation; Brazil; new evidence; combining; survey; fiscal data; 2001; 2015